Perkembangan Pasar Jongkok di Tembilahan (2000-2020) - Mulya Ayu Wandira; Etmi Hardi (Jurusan Sejarah FIS UNP, 2021)
Abstract This study discusses the Jongkok Market which is one of the traditional markets located in Tembilahan, Indragiri Hilir Regency, Riau Province from 2000-2020. Seeing the development of the Squat Market and its dynamics and its impact on the economy for the Tembilahan community. The purpose of this study is to reveal the background of the emergence of the Jongkok Market in Tembilahan, the development of the Jongkok Market from 2000-2020 and its influence on the economy of the Tembilahan community. This research includes historical qualitative research, using historical methods in the form of library research, archives and interviews. From the discussion, it can be seen that, First, the squat market is a traditional market that sells imported used goods. With a geography like this, it makes it easier for people to interact with traders from abroad, one of which is Singapore. Second, the emergence of the Squat Market was motivated by the large number of used clothing trading activities in Tembilahan, then in its development there were many factors supporting the existence of second-hand goods to increase the economy in the Jongkok Market since the 2000s. Third, the development of the Squat Market subsequently experienced changes in traders and types of merchandise. Changes in the types of merchandise sold in the Jongkok Market are influenced by various factors, the difficulty of getting PJ makes people start to switch to selling new goods which causes changes in the market, this also affects the increase in the number of traders in the Jongkok Market. The existence of this Squat Market also has an impact on the economy of the surrounding community. The creation of new job opportunities for the surrounding community and in addition to the creation of social relations between communities both locally and outside the city. Keywords: Development, Squatting Market, Community Economy.